(untitled) (Eurasian Journal of Philology Science and Education, 2016)
About genre signs and features, evolution, the ways of development, sources of an origin of the dastan epos are told in the article which are so often found in the Kazakh folklore. Authors of article, distinguishing love and liroepic genres, proceeding from their essence, a form and genre features, set as the purpose the analysis of works of this genre. In article it is said that east plots which are been the basis for a dastan and plots of the Kazakh dastan using actually primordial motives have essential distinctions, for example, the Kazakh dastans have other form, volume, poetic system, novelty in development of a plot, creative searches, a peculiar handwriting of his execution, means and ways of formation of a dastan. At the same time, it is proved in numerous works local legends and stories, original historical events from life of Kazakhs, the facts, tranformation. In final sense on the basis of researches by specialists in folklore of regularities of a genre, and also proceeding from own installations of article`s authors, some works of this genre are considered from typological positions.